FUZZY DIRECTED AND WEAKLY DIRECTED BAIRE SPACES - E. Poongothai; M. Nalini (Utilitas Mathematica, 2025)
We study fuzzy directed Baire spaces and weakly directed Baire spaces on fuzzy topological spaces. A characterization of fuzzy directed Baire spaces is given using fuzzy Gδ- sets. Further, we prove that the weakly directed Baire spaces with a directed Baire spaces. Also we discuss several characterizations of other fuzzy spaces namely fuzzy P- space, fuzzy hyperconnected space.